Things I wish I'd known: desiderata for early career psychiatrists. (February 2017) - Ng, Lillian; Steane, Richard; Chacko, Emme; Scollay, Natalie
Objective: The objective of this study was to disseminate advice imparted to early career psychiatrists by a panel of senior colleagues at a Royal Australian and New Zealand College of Psychiatrists symposium, reflecting on things they wished they had known at the earlier stage in their careers. Methods: Key themes were extracted from notes taken at the symposium, where opinions were expressed by three senior psychiatrists. Results: There are components in building a sustainable career as a psychiatrist, which include considering one's work environment and relationships with colleagues; self-care, mentorship and reflective practice; and seeking opportunities to teach and research for career progression. Conclusions: The mentorship and advice from senior colleagues can be highly influential. In order to sustain a career that has reward, meaning and longevity, psychiatrists would do well to pay attention to aspects of self-care, stay connected to their loved ones, seek an optimal work–life balance and take an interest in their long term career plans.